From Discontinuation to Commitment: A Participatory Model for Contraceptive Adherence - Sariati, Yuseva (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Contraceptive discontinuation remains a critical challenge in reproductive health programs, threatening program sustainability and maternal health outcomes. Transforming patterns from discontinuation to sustained commitment requires innovative health promotion models that address multi-dimensional factors influencing contraceptive behavior. Understanding the pathway from discontinuation to continuity is essential for designing effective, context-specific interventions. Purpose: This study aimed to design a comprehensive health promotion model that transforms contraceptive discontinuation patterns into sustained commitment among acceptors in Malang Regency, Indonesia, utilizing Health Belief Model and Social Cognitive Theory as theoretical foundations Methods: An exploratory qualitative study using Grounded Theory methodology was conducted through Focus Group Discussions (FGDs) involving key stakeholders including heads of Population and Family Planning Department, health center directors, midwives, Family Planning Field Officers (PLKB), and community health workers in Malang Regency. Data analysis followed the three-stage Grounded Theory coding process: open coding, axial coding, and selective coding. Results The designed health promotion model encompasses five interconnected dimensions grounded in Health Belief Model and Social Cognitive Theory: Individual Factors (knowledge, attitudes, self-efficacy), Environmental Factors (social support, healthcare accessibility), Behavioral Factors (observational learning, reinforcement), Perceptions (perceived risks, benefits, barriers), and Sustained Participation in Contraceptive Services. The transformation pathway "from discontinuation to commitment" was achieved through innovative strategies including the "Susimilek" program (husband involvement in contraceptive selection), community health worker engagement, and data-driven policy interventions. The model demonstrates how addressing multi-level determinants can convert discontinuation patterns into sustained contraceptive commitment, particularly addressing cultural, geographical, and structural barriers specific to Indonesian context. Conclusion: The designed health promotion model provides a comprehensive theoretical and practical framework for transforming contraceptive discontinuation patterns into sustained commitment through evidence-based, multi-level interventions. This culturally-sensitive model offers practical guidance for contraceptive services to enhance continuation rates and build long-term commitment among acceptors in similar low-middle income country contexts.